2015
DOI: 10.1177/1075547015609322
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Participate in an Online Citizen Science Game

Abstract: Online citizen science projects have the potential to engage thousands of participants with scientific research. A small number of projects such as Foldit use an online computer game format. Motivation to participate in Foldit was investigated in a group of 37 players using an online survey, semi-structured interviews and participant observation. Results suggest that contributing to scientific research and an interest in science were among the most important motivations for participation. Interaction with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
152
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(172 citation statements)
references
References 55 publications
18
152
1
1
Order By: Relevance
“…For example, Raddick et al [2010] identified 12 motivations for participating in the Galaxy Zoo project, including contributiing to a science project, learning about astronomy, discovery of galaxies few people have seen, community (i.e., meeting people with similar interests), teaching (i.e., useful resource teaching others about astronomy), the beauty of galaxies, finding the work fun, vastness of space (i.e., enjoying considering the scale of the universe), helping (i.e., happy to help), the Zoo (i.e., interest in the Galaxy Zoo project), and astronomy and science (i.e., having general interest in the field). Curtis [2015] identified a similar set of motivations for the Foldit project, including contribution to science, background interest in science, intellectual challenge, curiosity, liking puzzles, liking computer games, to learn something new, friendly competition, visual appeal/aesthetics and relaxing. Reed et al [2013] identified three broader motives, social engagement, interaction with the website and helping.…”
Section: Theory: Motivations Of Citizen-science Volunteersmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Raddick et al [2010] identified 12 motivations for participating in the Galaxy Zoo project, including contributiing to a science project, learning about astronomy, discovery of galaxies few people have seen, community (i.e., meeting people with similar interests), teaching (i.e., useful resource teaching others about astronomy), the beauty of galaxies, finding the work fun, vastness of space (i.e., enjoying considering the scale of the universe), helping (i.e., happy to help), the Zoo (i.e., interest in the Galaxy Zoo project), and astronomy and science (i.e., having general interest in the field). Curtis [2015] identified a similar set of motivations for the Foldit project, including contribution to science, background interest in science, intellectual challenge, curiosity, liking puzzles, liking computer games, to learn something new, friendly competition, visual appeal/aesthetics and relaxing. Reed et al [2013] identified three broader motives, social engagement, interaction with the website and helping.…”
Section: Theory: Motivations Of Citizen-science Volunteersmentioning
confidence: 99%
“…First, we removed motivations that only a few participants in prior studies identified as their major motivations. For example, in Curtis [2015], only one or two of the participants identified friendly competition, visual appeal/aesthetics or relaxing as their motivations. Second, we removed motivations that seemed to specific to a particular project and could not be applied to citizen-science projects more generally.…”
Section: Theory: Motivations Of Citizen-science Volunteersmentioning
confidence: 99%
See 3 more Smart Citations